Rapid multiplication of Kasthuri turmeric (Curcuma aromatica Salisb.) through minisett technique and nursery management - Jessykutty, T S Aswathy, P C (Journal of Spices and Aromatic Crops, 2017)
The experiment was conducted at Vellayani (Kerala) during 2014 with an objective to standardize minisett method of propagation and nursery techniques for rapid mass multiplication of Kasthuri turmeric. The investigation was taken up as two experiments. In experiment I best pre-sprouting treatments for rhizomes and in experiment II best soil-less coir pith based nursery mixtures for growth of Kasthuri turmeric seedlings were studied. The result indicated that rhizome bits with three node (approximate weight -7g) subjected to pre-treatments with benzyl adenine 100 ppm for 24 hrs was recorded the highest sprouting (95.60%). The improved method of protray seedling production using sprouted rhizome bits and coirpith + vermicompost + Trichoderma (1:25) media in 1:1 combination resulted in sturdy, uniform and healthy seedlings for transplanting in the main field.